Dopaminergic Projections From the Ventral Tegmental Area to the Nucleus Accumbens Modulate Sevoflurane Anesthesia in Mice - Gui, Huan; Liu, Chengxi; He, Haifeng; Zhang, Jie; Chen, Hong; Zhang, Yi (Frontiers in Cellular Neuroscience, 2021)
The role of the dopaminergic pathway in general anesthesia and its potential mechanisms are still unknown. In this study, we used c-Fos staining combined with calcium fiber photometry recording to explore the activity of ventral tegmental area (VTA) dopaminergic neurons (VTA-DA) and nucleus accumbens (NAc) neurons during sevoflurane anesthesia. A genetically encoded dopamine (DA) sensor was used to investigate the function of the NAc in sevoflurane anesthesia. Chemogenetics and optogenetics were used to explore the role of the VTA-DA in sevoflurane anesthesia. Electroencephalogram (EEG) spectra, time of loss of righting reflex (LORR) and recovery of righting reflex (RORR) were recorded as assessment indicators. We found that VTA-DA and NAc neurons were inhibited during the induction period and were activated during the recovery period of sevoflurane anesthesia. The fluorescence signals of dopamine decreased in the induction of and increased in the emergence from sevoflurane anesthesia. Activation of VTA-DA and the VTADA-NAc pathway delayed the induction and facilitated the emergence，accompanying with the reduction of delta band and the augment of gamma band. These data demonstrate that VTA-DA neurons play a critical role in modulating sevoflurane anesthesia via the VTADA-NAc pathway.